The Implementation Of Zakat Utilization Model Canvas (ZUMC) As A Fundraising Strategy In Amil Zakat Institutions In Southeast Sulawesi - Hakim, Miftahur Rahman; Zamani, Istiqomah Shariati; Amanah, Rawdatul; Zulhaja, Isya; Lestari, Azwah Tri (Magister Manajemen STIE Bank BPD Jateng, 2025)
This research seeks to explore the fundraising strategies employed by Amil Zakat Institutions (LAZ) in Southeast Sulawesi through the application of the Business Model Canvas approach, which has been adapted using the Social Enterprise Model Canvas framework—collectively referred to as the ZakatUtilization Model Canvas (ZUMC). The study focuses on two institutions: Baitul Maal Hidayatullah (BMH) and Wahdah Inspirasi Zakat (WIZ). A descriptive qualitative method was adopted, utilizing data collection techniques including observation, interviews, and documentation. The findings reveal that strategicpartnerships with government bodies such as Baznas and the Ministry of Religious Affairs, as well as private entities like PLN and Telkomsel, play a crucial role in enhancing zakat fundraising effectiveness. Moreover, diversification of funding sources and the integration of digital technology have proven to expand outreach and strengthen the transparency of zakat distribution. The implications of this study highlight the need for stronger collaboration among government, private, and community sectors in managing zakat to ensure more effective and efficient distribution. In addition, the use of digital tools in zakat fundraising contributes significantly to wider access and increased transparency, which in turn fosters greater public trust and engagement..